Integrasi Kurikulum Modern dan Nilai Tauhid: Analisis Konseptual dalam Pendidikan Islam Kontemporer - Syahrial; Halida; Abhanda Amra (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of a modern curriculum oriented towards 21st-century competencies demands the integration of spiritual values ​​so that education emphasizes not only intellectual aspects but also character building and tawhid awareness. This study aims to examine the integration of the modern curriculum with tawhid values ​​from an Islamic educational perspective. The study used a qualitative approach through library research. Data sources were obtained from books, national and international journal articles, and educational documents relevant to the modern curriculum and Islamic education. Source selection was based on the relevance of the theme, academic credibility, and the recency of the publication. Data were analyzed using content analysis techniques through a process of data reduction, categorization, interpretation, and synthesis. The results of the study indicate that the integration of the modern curriculum and tawhid values ​​can be realized through a holistic educational approach that combines spiritual, intellectual, moral, and social dimensions. This integrative curriculum is not only oriented towards academic achievement but also character building, spiritual awareness, and social responsibility of students in facing global challenges.